CREUTZFELDT -JAKOB HASTALIĞI: OTOPSİ SUNUMU VE LİTERATÜRÜN GÖZDEN GEÇİRİLMESİ - ÖZ, Büge; ERSOY, Gökhan; DEMİRKESEN, Cuyan (Cerrahpaşa Medical Journal, 2014)
Background.- Creutzfeldt-Jakob disease (CJD) is a very rare untreatable progressive neurodegenerative disorder. Its incidence is one in 1 million per year in European countries, which is rarer in Turkey. It is associated with the presence of a protein in the brain, incompletely defined transmissible agent, called as prion. Observation.- An autopsy case of 64 years old man was presented. Grossly there was a severe cortical atrophy in the brain especially in the frontal and temporal lobes. Histopathological sections showed spongiform changes and neuronal loss in the gray matter. Immunohistochemical examination revealed synaptic and plaque like prion protein (PrP) accumulation in the cortex and severe reactive astrogliosis which was positive for GFAP.